1989
DOI: 10.1002/anr.1780320608
|View full text |Cite
|
Sign up to set email alerts
|

A reexamination of the effectiveness of self‐care education for persons with arthritis

Abstract: We examined the effectiveness of 2 models of arthritis self-care intervention, the home study model and the small group model. The effects of disease diagnosis and duration, self-care behavior, perceived helplessness, social support, treatment choice, and formal education level on outcomes among persons with arthritis who participated in these programs were evaluated. A pretest-posttest control group design was utilized in the initial experimental study; comparison group designs were used in the longitudinal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
2
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 20 publications
2
81
2
1
Order By: Relevance
“…To date, the limited evidence is that individual education is less effective -improving knowledge and patient satisfaction but not self-efficacy, health behaviours or health status (Riemsma et al, 1997(Riemsma et al, , 2002. Self-study programmes are effective when individualized but require health professional input to support people through change (Goeppinger et al, 1989;Fries et al, 1997). Why: The potential long-term benefits to the person and society of taking responsibility for self-management must be emphasized from an early stage, so that people attend effective group programmes.…”
Section: Effectiveness Of Rehabilitation Interventionsmentioning
confidence: 99%
“…To date, the limited evidence is that individual education is less effective -improving knowledge and patient satisfaction but not self-efficacy, health behaviours or health status (Riemsma et al, 1997(Riemsma et al, , 2002. Self-study programmes are effective when individualized but require health professional input to support people through change (Goeppinger et al, 1989;Fries et al, 1997). Why: The potential long-term benefits to the person and society of taking responsibility for self-management must be emphasized from an early stage, so that people attend effective group programmes.…”
Section: Effectiveness Of Rehabilitation Interventionsmentioning
confidence: 99%
“…The relationship of changes in knowledge to long-term improvements in pain and functioning, however, does not appear to be strong. Goeppinger and colleagues [16] found that arthritis education led to improvements in arthritis knowledge, self-care behaviors, and feelings of helplessness. Although these improvements were sustained at 12-months follow-up, concomitant reductions in pain, depression, and function were not evident.…”
Section: Outcomes Of Educational Intervention Alonementioning
confidence: 99%
“…The literature on spousal training in arthritis pain management is, in fact, quite limited. Only three arthritis education studies have included spouses in educational group sessions for arthritis patients [13,16,34]. None of these studies trained spouses to assist patients in their use of pain coping skills.…”
Section: Evaluating Behavioral Interventions For Enhancing Maintenancementioning
confidence: 99%
“…Several studies have indicated that arthritis education increases knowledge level (3,(8)(9)(10)(11)(12)(13)(14)(15) but have been inconclusive about the relationship between increased knowledge and positive changes in behaviors (3,101. Other studies have indicated that changes in behaviors may substantially improve health status (7,11,16,17).…”
mentioning
confidence: 99%